Analysis of Mitigation Strategies For Project Delay Factors In The Probolinggo Square Construction - Laksana Putra, Negarawan; Patriadi, Andi; Sajiyo, Sajiyo (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the mitigation of factors that cause delays in the Probolinggo City Square construction project, a project that faces challenges in implementation and completion. Delays in construction projects can have various negative impacts, including increased costs, time losses, and reduced quality of project outcomes. Thus, project mitigation becomes the main core in this research. Through this research, it is shown that there are several mitigation measures, such as digitization of administrative processes to speed up approval of materials, improved coordination between parties to reduce conflicts and uncertainties, and more careful planning for additional work and identification of work. In addition, workforce training and the use of more advanced project management technology can improve the efficiency of project implementation. The results of this study are expected to be a reference for parties involved in construction projects, especially in managing the risk of delay. With the implementation of appropriate mitigation measures, construction projects can be more efficient in terms of time, cost, and quality, thus providing maximum benefits for all parties involved.